Quartz job scheduling framework building open source enterprise applications - Cavaness, Chuck (Pearson Education, 2006)
Annotation
Print version record
Keywords: Quartz (Electronic resource); Production scheduling; Open source software; Ordonnancement (Gestion); Logiciels libres